1998
DOI: 10.1038/sj.onc.1201987
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase activity during spontaneous immortalization of Li-Fraumeni syndrome skin fibroblasts

Abstract: Li-Fraumeni Syndrome (LFS) is characterized by heterozygous germline mutations in the p53 gene. Accompanied by genomic instability and loss or mutation of the remaining wild type p53 allele, a low frequency of spontaneous immortalization in LFS ®broblasts occurs. It is believed that the loss of p53 wild type function contributes to immortalization of these LFS ®broblasts, but it is not clear if this is su cient. Because stabilization of telomere length is also thought to be a necessary step in immortalization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 43 publications
1
46
1
Order By: Relevance
“…Total proteins (20 mg) were used for SDS-PAGE and individual proteins were visualized after immunoblotting using specific antibodies senescence, indicating that in human fibroblasts, the p53 pathway is not essential for PML-induced senescence. Given the extensive literature implicating p53 in the senescent response of fibroblasts (Gollahon et al, 1998;Campisi, 2001), our results were surprising. However, p53 was reported to be nonessential for the senescent response of human fibroblasts to oncogenic ras (Serrano et al, 1997) or telomere deprotection (Smogorzewska and de Lange, 2002).…”
Section: Discussioncontrasting
confidence: 42%
“…Total proteins (20 mg) were used for SDS-PAGE and individual proteins were visualized after immunoblotting using specific antibodies senescence, indicating that in human fibroblasts, the p53 pathway is not essential for PML-induced senescence. Given the extensive literature implicating p53 in the senescent response of fibroblasts (Gollahon et al, 1998;Campisi, 2001), our results were surprising. However, p53 was reported to be nonessential for the senescent response of human fibroblasts to oncogenic ras (Serrano et al, 1997) or telomere deprotection (Smogorzewska and de Lange, 2002).…”
Section: Discussioncontrasting
confidence: 42%
“…MDAH041 LFS cells contain significant telomerase activity after immortalization (Gollahon et al, 1998). Although in microarray analysis, the hTERT gene for the protein of enzymatic subunit of telomerase was not significantly upregulated after immortalization of MDAH041 cells, 1.6-fold, we found using Q-RT-PCR that there was a significant increase in hTERT expression, 486-fold (Table 2).…”
Section: Discussionmentioning
confidence: 82%
“…46 Additionally, telomerase activity was unaffected by overexpression of p53 in immortalized endothelial cells. 47 Conversely, it was reported that induced expression of wild-type p53 resulted in the down-regulation of telomerase activity in not only immortalized fibroblasts, 48 but also cancer cell lines. 49,50 Furthermore, it has recently been demonstrated that severe telomere shortening in telomerase-deficient mice activated p53, leading to growth arrest and/or apoptosis.…”
Section: Discussionmentioning
confidence: 99%